Influence of the β- Radiation/Cold Atmospheric-Pressure Plasma Surface Modification on the Adhesive Bonding of Polyolefins - Bednarik, Martin; Mizera, Ales; Manas, Miroslav; Navratil, Milan; Huba, Jakub; Achbergerova, Eva; Stoklasek, Pavel (Materials (Basel, Switzerland), 2020)
The goal of this research was to examine the effect of two surface modification methods, i.e., radiation cross-linking and plasma treatment, on the adhesive properties and the final quality of adhesive bonds of polypropylene (PP), which was chosen as the representative of the polyolefin group. Polymer cross-linking was induced by beta (accelerated electrons-β-) radiation in the following dosages: 33, 66, and 99 kGy. In order to determine the usability of β- radiation for these applications (improving the adhesive properties and adhesiveness of surface layers), the obtained results were compared with values measured on surfaces treated by cold atmospheric-pressure plasma with outputs 2.4, 4, and 8 W. The effects of both methods were compared by several parameters, namely wetting contact angles, free surface energy, and overall strength of adhesive bonds. Furthermore, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) were conducted. According to our findings the following conclusion was reached; both tested surface modification methods significantly altered the properties of the specimen's surface layer, which led to improved wetting, free surface energy, and bond adhesion. Following the β- radiation, the free surface energy of PP rose by 80%, while the strength of the bond grew in some cases by 290% in comparison with the non-treated surface. These results show that when compared with cold plasma treatment the beta radiation appears to be an effective tool capable of improving the adhesive properties and adhesiveness of PP surface layers.
Keywords: free surface energy; radiation cross-linking; plasma treatment; β− radiation; wetting contact angle; adhesion; polypropylene; bonded joints